Travelling Through Time on My Quest to be a Children’s Author - Charlotte Teeple-Salas (Leaf Journal)
In her quest to become a published children’s author, Charlotte Teeple-Salas explores why she is compelled to write time-slip stories, and whether their appeal in the publishing industry is a passing trend, cyclical or enduring. Includes thoughts on writing her current project, a romantic Young Adult (YA) time-slip suspense.